Diversity, Distribution Pattern and Conservation of Pteridophytes in Mehao Wildlife Sanctuary, Arunachal Pradesh - Rawat, Vineet Kumar; Sahu, T. R. (Indian Forester, 2009)
Maximum number of Pteridophytic diversity observed in Himalayan region and most Protected Areas of the Indian Himalayan Region have not received much attention in terms of floristic exploration. In Mehao Wildlife Sanctuary (MWLS) comprehensive studies on diversity, distribution pattern, habitat preference, rarity and conservation status of the Petridophytes have been carried and 205 species of Pteridophytes were recorded. The altitudinal distribution of the species revealed that the maximum numbers of species were present in the subtropical to temperate zone (900-3500m) and a decrease in diversity was noticed with increasing altitude. Terrestrial habitats showed maximum species richness and twenty one pteridophytic species had been identified as rare-endangered.